The Role of Nonmetastatic Lymph Nodes in the Survival of Colorectal Cancer: A Systematic Review - Alexander J. Pennings, MSc; Brecht A. van der Velden, BSc; Maximilian Kloft, MSc; Loes F. S. Kooreman, MSc; Jos M. P. Kleijnen, PhD; Stephanie O. Breukink, PhD; Geerard L. Beets, PhD; Heike I. Grabsch, PhD; Jarno Melenhorst, PhD (Annals of Surgery Open)
Objective:. In this review, we aim to provide an overview of literature on lymph node (LN) histomorphological features and their relationship with the prognosis in colorectal cancer (CRC). Background:. Lymph nodes play a crucial role in the treatment and prognosis of CRC. The presence of LN metastases considerably worsens the prognosis in CRC patients. Literature has shown that the total number of LNs and the number negative LNs (LNnegs) has prognostic value in CRC patients. In esophageal carcinoma, LN size seems to be surrogate of the host antitumor response and a potentially clinically useful new prognostic biomarker for (y)pN0 esophageal carcinoma. Methods:. A comprehensive search was performed in Pubmed, Embase, Medline, CINAHL, and the Cochrane library in March 2021. The PRISMA guidelines were followed. Only studies focusing on histomorphological features and LN size and their relation to overall survival were selected. Results:. A total of 9 unique articles met all inclusion criteria and were therefore included in this systematic review. Six of these studies investigated HMF (eg, paracortical hyperplasia, germinal center predominance, and sinus histiocytosis) and 4 studies LNneg size and their relationship with overall survival. The presence of paracortical hyperplasia and an increased number of large LNnegs is related to a more favorable prognosis in CRC. Conclusion:. The results of this systematic review seem to support the hypothesis that there is a relationship between the host antitumor response reflected in different histomorphological reaction patterns visible in LNnegs and LNneg size related to survival in CRC patients.